Regionális fejlődés, külföldi tőke és feketegazdaság a győri térségben - Nagy, Réka (Szociológiai Szemle, 2024)
Studies dealing with the possibilities and limits of regional development of transforming the East-European countries have gained importance in recent years. This paper mainly discusses the indirect and direct impacts of foreign capital investment on the socio - economic development in the Győr region. The author seeks answers - based on social theory, historical perspective and empirical research - to the successful development of the chosen region. A substantial part of the paper consists of the complex action of local governance for attracting investments, and to regulate the local market accordingly. The effectiveness of the local regulation related the formerly important illegal marketplace ("Polish market") is a good example of this action.